Faktor-Faktor Yang Berhubungan dengan Kejadian Demam Berdarah Dengue (DBD) di Kecamatan Ngampilan Kota Yogyakarta Tahun 2011 - Luis Anggraini; Narto Narto; Sri Puji Ganefati (Poltekkes Kemenkes Yogyakarta, 2012)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus and spread by Aedes aegypti and Aedes albopictus mosquitoes. Among the 14 kecamatans in Yogyakarta City, Ngampilan was one of the highest cases of DHF in 2011, i.e. 38 cases. This study was aimed to understand the factors related with those DHF incidence by conducting an obser-vational study employed case-control design with retrospective approach. The number of study subjects in both the case and control groups were 38. Data were obtained through interview and observation. Odds Ratio and logistic regression were used to analyse the data. Results from bi-variate analysis showed that among the observed variables, those which were significantly cor-related with DBD incidence were: the presence of mosquito larvae habitat, and age, attitude and prevention behavior of respondents. Furthermore, multivarite analysis revealed that the most do-minant factors were the existence of mosquito larvae habitat (OR=4,526, 95 % CI=1,352-13,372, p=0,006); and respondents’ age (OR=4,645, 95 % CI=1,263-17,088, p=0,021). People aged less than 15 years old and close with Aedes larvae’s habitat have probability of getting DBD as much as 31,32%.